Smart teachers, successful students? A systematic review of the literature on teachers' cognitive abilities and teacher effectiveness. (June 2020) - Bardach, Lisa; Klassen, Robert M.
Abstract: This study provides a systematic review of the literature on teachers' cognitive abilities (intelligence test scores and proxies of cognitive abilities such as college entrance exam scores and basic skills test scores) and teacher effectiveness. Twenty-seven studies conducted between 2000 and 2019 constitute the sample for this review. Studies using intelligence test scores were rare, with the results indicating no or negative associations with teacher effectiveness. Studies on proxies of cognitive abilities yielded, at most, small positive relations with teacher effectiveness. However, behind these overall results regarding proxies of cognitive abilities lie interesting heterogeneities, as several studies analyzing different test domains uncover a differentiated pattern of findings. We also identify key limitations related to construct measurement, sampling approaches, statistical analyses and the interpretation and reporting of the included studies, and outline a path for future research on teachers' cognitive abilities and teacher effectiveness. Highlights: A systematic review of teachers' cognitive abilities and teacher effectiveness was conducted. Intelligence test scores and proxies of cognitive abilities (college entrance exam and basic skill test scores) considered. There were no (or negative) relations between intelligence test scores and teacher effectiveness. Proxies of cognitive abilities yielded, at most, small positive relations with teacher effectiveness. Numerical abilities may have potential usefulness as a predictor of teacher effectiveness.